Comparison of efficacy of conjugated estrogen cream 0.625% plus clobetasol 0.05% vs. clobetasol 0.05% alone in the treatment of vitiligo patients - Asilian, A.; Shabaram, M.; Faghihi, G. (Journal of Pakistan Association of Dermatologists, 2016)
Background: Vitiligo is a pigmentary skin disorder characterized by hypo- or depigmented patches. Topical steroid creams are used as a common standard method in vitiligo therapy. Â Objective The goal of this study was to compare the efficacy of topical clobetasol (as a standard method for treatment of vitiligo) versus combination of clobetasol + topical estrogen in treatment of vitiligo. Â Patients and methods In this double-blind clinical trial, 37 patients who had at least 2 vitiligo patches were treated with topical clobetasol on one side of the body for three months while a combination of clobetasol and estrogen was applied on the other side. Three months after termination of therapy, the patients were visited again for improvement of disease. The results were evaluated with statistical analysis of paired t test, McNemar and Wilcoxon tests in SPSS software. Â Results Overall 37 patients, 21 women and 16 men with minimum age of 14 and maximum of 45 years old, completed the study. The difference of average area of lesions before and after treatment in clobetasol and estrogen group was significantly more than clobetasol only group (P=0.001). There was no significant difference between clobetasol and clobetasol + estrogen treatment for two age groups of 14-30 and 31-45 years. Also the pigmentation score of two treatment groups measured by paired sample test was not significant for both sexes (P> 0.05). Â Conclusion Addition of estrogen to clobetasol increases its efficiency in treatment of vitiligo without any side effects. Also it seems that estrogen may decrease the topical clobetasol complications such as atrophy, erythema and telangiectasia. Â